1993
DOI: 10.1007/bf00166943
|View full text |Cite
|
Sign up to set email alerts
|

Frequency- and train length-dependent variation in the roles of postjunctional ?1- and ?2-adrenoceptors for the field stimulation-induced neurogenic contraction of rat tail artery

Abstract: The present paper examines the roles of postjunctional alpha 1- and alpha 2-adrenoceptors for the noradrenaline (NA)-induced neurogenic contractile response to field stimulation mainly with 1-100 pulses at 2 or 20 Hz, in the tail artery of adult normotensive rats. Pharmacological tools were employed to isolate and characterize the alpha 1- and alpha 2-adrenoceptor-mediated components of this response. The degree to which the drugs influenced NA release or reuptake was assessed by their effects on the electroch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
29
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 54 publications
8
29
0
Order By: Relevance
“…We have also reported that a,-MeATP strongly increased the amplitude of the NA-mediated neurogenic contraction. The potentiating effect was more marked on the al-than on the X2-adrenoceptor-mediated component of this response; during stimulation at 20 Hz it was inversely related to the train length 1993a). A similar potentiating effect of oE,j-MeATP on the neurogenic contraction has been reported to occur in other vascular tissues and in vas deferens (Bulloch et al, 1990;MacDonald et al, 1992).…”
Section: Introductionsupporting
confidence: 69%
See 3 more Smart Citations
“…We have also reported that a,-MeATP strongly increased the amplitude of the NA-mediated neurogenic contraction. The potentiating effect was more marked on the al-than on the X2-adrenoceptor-mediated component of this response; during stimulation at 20 Hz it was inversely related to the train length 1993a). A similar potentiating effect of oE,j-MeATP on the neurogenic contraction has been reported to occur in other vascular tissues and in vas deferens (Bulloch et al, 1990;MacDonald et al, 1992).…”
Section: Introductionsupporting
confidence: 69%
“…These effects probably do not interfere with the neurogenic contraction in rat tail artery, however, because the P2Y-purinoceptor antagonist reactive blue 2 (Burnstock & Warland, 1987) did not at 10-50 JM concentrations significantly affect the neurogenic contraction of rat tail artery caused by 10 pulses at 20 Hz, or the enhancing effect of a,-MeATP on the contraction (n = 3, not shown), and because P2z-purinoceptors do not seem to exist on smooth muscle cells (see Gordon, 1986). The following findings in the present study indicate that the effects of suramin were due to block of the P2x-purinoceptor- (Bao et al, 1989;1993a Leff et al, 1990). Addition of the K+-channel blocker, tetraethylammonium, greatly amplified the ATP-as well as NA-induced components of the neurogenic contraction, probably by dramatically increasing the release of both NA and ATP Stjiirne et al, 1990) and the excitability of the smooth muscle (Haeusler & Thorens, 1980 (Bao et al, 1993b) and that the ATP-mediated contractile response faded rapidly during long high frequency trains (Bao et al, 1993b), probably as a result of decline in per pulse release of ATP .…”
Section: Recording Of Contractile Responsessupporting
confidence: 64%
See 2 more Smart Citations
“…However, in the latter preparation the sensitivity of the response to the selective a 2 -adrenoceptor antagonist, RX-811059 (Mallard et al, 1992), indicates a role for postjunctional a 2 -adrenoceptors in addition to a 1 -adrenoceptors. These ®ndings agree with earlier reports by several other groups (Medgett et al, 1983;Rajanayagam et al, 1990;Bao et al, 1993). In the guinea-pig isolated ileum, a well recognized model of cholinergic neurotransmission, the electrically-evoked responses were abolished by the muscarinic receptor blocker atropine.…”
Section: Discussionsupporting
confidence: 92%